2013
DOI: 10.1371/journal.pone.0061718
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Health System Development and the Burden of Cardiovascular Disease: An Analysis of WHO Country Profiles

Abstract: BackgroundSeveral risk factors for cardiovascular disease (CVD) have been identified in recent decades. However, the association between the health system and the burden of CVD has not yet been sufficiently researched. The objective of this study was to analyse the association between health system development and the burden of CVD, in particular CVD-related disability-adjusted life–years (DALYs).MethodsUnivariate and multivariate generalized linear mixed models were applied to country-level data collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…An analysis of the relationship between health care worker density (including physicians, nurses, and others) and CVD outcomes reported that a univariate analysis revealed that health care worker density is associated with better CVD outcomes, although a multivariable analysis yielded the opposite relationship. 18 Another study reported no significant relationship between physician density and medical guideline adherence (including for CVD) in Germany. 19 Current estimates of global health care worker shortages have largely not taken into account the human resource requirements for managing NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the relationship between health care worker density (including physicians, nurses, and others) and CVD outcomes reported that a univariate analysis revealed that health care worker density is associated with better CVD outcomes, although a multivariable analysis yielded the opposite relationship. 18 Another study reported no significant relationship between physician density and medical guideline adherence (including for CVD) in Germany. 19 Current estimates of global health care worker shortages have largely not taken into account the human resource requirements for managing NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Недостаточное финансирование здравоохранения (как государством, так и частными лицами), по некоторым данным, является ключевым предиктором смертности и потерь в качестве жизни, в т.ч. и по причине ССЗ [21,22]. Даже без фактического подтверждения представляется очевидным, что увеличение затрат на здравоохранение должно привести к более широкому использованию населением медицинских технологий, сберегающих и поддерживающих здоровье.…”
Section: проблема 1 недостаточное финансирование здравоохраненияunclassified
“…Cardiovascular disease (CVD) is an increasingly frequent indirect cause of lost productivity [1], and one of the leading causes of death worldwide [2,3]. It is therefore essential to improve our prevention strategies because, although they are still not as efficacious as they might be, the feasibility of large-scale preventive interventions such as those promoted by the World Health Organisation (WHO) [4], should improve cardiovascular (CV) outcomes [5].…”
Section: Introductionmentioning
confidence: 99%